Structural and Morphological Studies of Lava Rock from Mount Gamalama Ternate for Possible Functional Materials Applications - Malik Anjelh Baqiya; Iqbal Limatahu; Muhammad Nasrun; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
A large eruption of Mount Gamalama happened nearly 350 years ago has left the frozen lava rocks that are now spread in the form of black stone located in the North-East coast of the island of Ternate, called batu angus (Angus stone). This paper reports the basic analysis including the phase content, crystal structure and particle morphology of the frozen lava rock, Angus stone, briefly. Based on the XRD pattern, Angus stone contains up to 20% of magnetic phases. The analysis of XRF and XRD data reveals that there are dominantly non-magnetic phases (silicate phases) in the Angus stone with the combination of Si-Al-K-Ca-O elements. Elemental distribution map from SEM/EDX image shows that there is a clear separation between non-magnetic and magnetic phases in the crushed powders indicating the easiness to obtain both phases separately. This study proves that Angus stone has potential application as a base material for the preparation of magnetic and non-magnetic functional materials.